Islamic Law and Sustainable Development Goals - Sohaib Mukhtar; Zinatul Ashiqin Zainol; Sufian Jusoh (Institute for Research and Community Empowerment (LPPM TAZKIA), 2018)
This study aims to analyze Sustainable Development Goals (SDGs) prescribed by United Nations Development Program (UNDP) under Islamic Law. This paper is qualitative method of research analyzing SDGs under verses of Holy Qur’an and traditions of Prophet Muhammad ﷺ. This study found that what SDGs ask member states to do has been prescribed in Holy Qur’an and Sunnah of Prophet Muhammad ﷺ way back 1400 years ago and demanded by Almighty Allah and the last Prophet Muhammad ﷺ for eradication of poverty, hunger, malnutrition etc. Islamic law prohibits usury, gambling, uncertainty and other illegal activities to protect poor people of the society against rich landlords. Therefore, member states are required to follow SDGs to achieve peace, harmony and economic growth for betterment of humanity which is also a duty under verses of Holy Qur’an and traditions of Prophet Muhammad ﷺ to achieve success in this world and in the hereafter.